QoS-aware architecture for FHMIP micromobility - Lopes, Nuno Vasco (2009)
Wireless networks will certainly run applications with strict QoS requirements and so, micro-mobility protocols such as fast hierarchical mobile IPv6 (FHMIP) are useful tools to accomplish this new feature. The FHMIP is an effective scheme to reduce Mobile IPv6 handover disruption, however it does not support application's QoS requirements. Therefore, in order to provide QoS guarantees for real-time applications it is necessary to develop new traffic management schemes; this implies the optimization of network mobility support and also some network congestion control. A traffic management scheme of this type should take into account the QoS requirements of handover users and should implement a resource management (RM) scheme in order to achieve this. In this paper, a new RM scheme for the DiffServ QoS model is proposed. This new scheme is implemented by access routers as an extension to FHMIP micromobility protocol. In order to prevent QoS degradation of the existing traffic, access routers should evaluate the impact of admitting a new mobile node (MN), previously to the handover. This evaluation and sequent decision on wether admitting or refusing MN's traffic is based on a measurement-based admission control (MBAC) algorithm. This architecture, that has been implemented and tested using ns-2, includes a simple signaling protocol, a traffic descriptor and exhibits an adaptive behavior to traffic QoS requirements. All the necessary measurements are aggregated by class-of-service, thus avoiding maintaining state on the individual flows.